2007
DOI: 10.1136/oem.2005.023952
|View full text |Cite
|
Sign up to set email alerts
|

Glycol ethers and semen quality: a cross-sectional study among male workers in the Paris Municipality

Abstract: This study suggests that most glycol ethers currently used do not impact on human semen characteristics. Those that were more prevalent from the 1960s until recently may have long lasting negative effects on human semen quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 34 publications
0
13
1
Order By: Relevance
“…In the present study, as in the previous Belgian and Dutch studies27 31 only some 5% of urine samples measured were positive for glycol ether metabolites (data not shown). The level of detection in these studies was however about 20 times less sensitive than in the recently published study of French municipal workers where methoxyacetic acid was found in the urine of 51.1% of men thought to be currently exposed (in 2000–1) to glycol ethers and 24.5% of those not currently exposed, with ethoxyacetic acid in the urine of 11.1% and 5.7% of men 28. Thus despite the documented reductions in both relative and absolute amounts of toxic glycol ether use, low exposures still appear to be widespread.…”
Section: Discussioncontrasting
confidence: 63%
“…In the present study, as in the previous Belgian and Dutch studies27 31 only some 5% of urine samples measured were positive for glycol ether metabolites (data not shown). The level of detection in these studies was however about 20 times less sensitive than in the recently published study of French municipal workers where methoxyacetic acid was found in the urine of 51.1% of men thought to be currently exposed (in 2000–1) to glycol ethers and 24.5% of those not currently exposed, with ethoxyacetic acid in the urine of 11.1% and 5.7% of men 28. Thus despite the documented reductions in both relative and absolute amounts of toxic glycol ether use, low exposures still appear to be widespread.…”
Section: Discussioncontrasting
confidence: 63%
“…Several studies in infertility clinics have identified occupational exposure to glycol ethers as a potential cause (e.g. Multigner et al 2007;Cherry et al 2008). Numerous studies in laboratory animals (e.g.…”
Section: Effects Of Environmental Chemicals On Spermatogenesis In Adumentioning
confidence: 99%
“…Another study conducted in Lebanon had demonstrated that occupational exposure to harmful physical and chemical agents is associated with increased risk of male infertility [22]. Exposure to organic solvents at work associated with reduction in count of motile sperm [23], a number of solvents that are used in industry may have an adverse effect on male reproductive function like carbon disulphide that had shown to affect semen quality but in low exposures had shown no effect [24]. Previous exposure to glycol ethers in work place associated with decrease in the semen quality [25].…”
Section: Occupational Exposurementioning
confidence: 99%